Kecenderungan tingkat keterampilan berpikir siswa SMA menurut taksonomi bloom dan kaitannya dengan gender - Rolina Amriyanti Ferita; Mia Fitria (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This study aims to get an overview of the level of thinking of high school students in terms of Bloom's revised taxonomy and see its relation to gender. The type of research conducted is Quantitative Descriptive with the Ex Post Facto approach, which is research conducted to examine events that have occurred which then traces back to find out the factors that can lead to these events. The event referred to in this study is HOTS students, while the factors that can lead to these events are gender. The results showed that there was no relationship between the level of students' thinking skills and their gender.